A 210Pb chronological study in sediments from poços de caldas alkaline massif (PCAM), Brazil - Matamet, F. R.M. [UNESP]; Bonotto, D. M. [UNESP] (Elsevier, 2018)
The Constant Flux and Constant Sedimentation (CF:CS) of supported/excess 210Pb model was successfully used to study sediment profiles from Antas stream, located in the region of Poços de Caldas city, Minas Gerais State, Brazil. Historical changes in the region were tracked from evaluating the sedimentation rate by the 210Pb method. In that site, Osamu Utsumi mine was the first mining-industrial complex for the production of concentrated uranium in Brazil. Four sediment testimonies were sampled along Antas stream in order to determine sedimentation rates using 210Pb as geochronometer. 210Pb and 238U activity concentrations were determined in sediment samples by alpha spectrometry, allowing to find the excess 210Pb present in the sediments. Additionally, the main oxides, organic matter, particles size and water composition were determined in order to assist the results interpretation from radionuclides data. The results allowed find one (profile PKS-4) or two (profiles PKS-1, PKS-2 and PKS-3) sedimentation rates, probably due to changes in the sediments input regime in the region. The sedimentation rates were in the range between 0.26 and 0.94 g/cm2.year, corresponding to the interval of linear sedimentation rate of 0.21 – 0.92 cm/year. The deposition year in the bottom of PKS-4 profile as estimated from the sedimentation rate coincided with the construction year of Bortolan dam (1956). Large touristic interventions carried out at Poços de Caldas city from 1920s coupled to unbridled urbanization, industrialization and demographic growth there in the second half of the twentieth century possibly caused the changes found in the sedimentation rates.
Keywords: Antas stream; Poços de Caldas plateau; Sedimentation rate; Unsupported/excess 210Pb model